Construction Of Drug Abuses (Case Study at Class 11-A Kupang Penitentiary) - Maria M. Tri Ratna Sari; Tari, Ezra; Natonis, Harun Y. (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Completers reported higher alcohol use than counterparts. Explores the model's subcategories: “life choices” (substance use, criminal and sexual behavior), static (background and disposition), and dynamic situational influences (occupation, psychological state, recent and past encounters).This research aims to determine the development of drug abuse in the Kupang Class II A Correctional Institution. The method used is an analytical descriptive approach . The data collection method is data from interviews and observations, the data analysis used is qualitative data analysis . The results of the research show that drug abuse guidance in Class IIA Kupang Prison has been achieved implemented in accordance with the Decree of the Minister of Justice of the Republic of Indonesia regarding the pattern of training prisoners/detainees of the Minister of Justice of the Republic of Indonesia, however, its implementation is still not perfect due to various obstacles. The training for narcotics prisoners has so far remained the same as the training for general prisoners . Drug abuse is a special case and should receive special guidance.